Use in a new receptor in functional bread making - Turg’unov, Shukrullo; Mallabayev, Odiljon (Scientific and Technical Journal of Namangan Institute of Engineering and Technology, 2024)
Functional foods have gained significant attention due to their potential health benefits. In this study, we investigate the incorporation of a novel receptor in bread making to enhance its functional properties. Our findings suggest that this receptor holds promise in improving the nutritional profile and sensory attributes of bread, thus offering a novel avenue for the development of functional bread products.